Analisis Rasio Efektivitas Pendapatan Masa Pandemi Covid-19 pada Wisata Persemaian Permanen Garahan (PPG) Cluster Durian Desa Sidomulyo Kecamatan Silo Kabupaten Jember - Susanti, Indria Yuli; Epriliyana, Nike Norma; Afandi, Alfi Khofifah (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2023)
The COVID-19 pandemic that started in 2020 has resulted in a decline in the economy in all sectors, including the tourism sector, due to restrictions on community activities. The purpose of this study was to analyze the level of income effectiveness ratio during the COVID-19 pandemic at the Garahan Permanent Nursery Tourism (PPG) Durian Cluster, Sidomulyo Village, Silo District, Jember Regency. This research is descriptive with a quantitative approach. To find out the level of effectiveness of income, the effectiveness ratio is calculated by comparing the realization of income receipts with the target of revenue receipts. Revenue receipts data used in this study are revenue receipts for 2021 and 2022. Based on the results of calculating the effectiveness ratio for revenue in 2021, a result of 100.035% is obtained, which means that revenue receipts for 2021 are very effective, while the effectiveness ratio for 2022 is 71.5%, which means they are in the less effective category.